Prevalence, risk factors for and clinical impact of persistent hyperCKemia in a general population. The Tromsø Study - Lilleng, Hallvard (Universitetet i Tromsø, 2014)
Papers 1 and 3 of this thesis are not available in Munin: 1. Lilleng H, Abeler K, Johnsen SH, Stensland E, Løseth S, Jorde R, Figenschau Y, Lindal S, Wilsgaard T, Bekkelund SI.: 'Variation of serum creatine kinase (CK) levels and prevalence of persistent hyperCKemia in a Norwegian normal population. The Tromsø Study', Neuromuscular Disorders (2011), vol. 21(7):494–500. Available at http://dx.doi.org/10.1016/j.nmd.2011.04.007 3. Lilleng H, Abeler K, Johnsen SH, Stensland E, Løseth S, Lindal S, Wilsgaard T, Bekkelund SI.: 'Clinical impact of persistent hyperCKemia in a Norwegian general population. A case control study', Neuromuscular Disorders (2013), vol. 23(1):29–35. Available at http://dx.doi.org/10.1016/j.nmd.2012.07.008